O exercício da autoridade do Estado no mar - Pargana, Miguel Xavier da Cunha Oliveira Júdice (2019)
Portugal owns a significant maritime zones under sovereignty and national jurisdiction, in which potentially exploitable resources exist and an amount of economic activities can be developed. For that reason, the State authority at sea is essential for the purpose of in view of military defense, maritime security and the promotion of State development. For the exercise of the state authority at sea, it is necessary to build a system of maritime authority, which in Portugal has undergone changes over time. Thus, the present work identifies the national maritime areas, develops the concept of maritime authority, presents the various actors of the system, as well as make proposals for the evolution of the actual national system.